Determinan Perilaku Seksual Berisiko pada Remaja Makassar (Studi Kasus Santri Darul Arqam Gombara dan SMAN 6) - Masni masni; St. Fatima Hamid (Media Kesehatan Masyarakat Indonesia, 2018)
Adolescence is a period great curiosity and want to try to imitate what they seen or heard. Curiosity makesteens more permissive to engage in risky sexual behavior, but it is suspected that religious understanding will bea distinguishing factor. This study aims to determine the influence of religious understanding, parent role, peerrole and the use of social media against risky sexual behavior in adolescents by comparing the santri MadrasahAliyah in Darul Arqam Gombara Pesantren with students of SMAN 6 Makassar. Observational research with crosssectional study design, involving 79 students of MA Darul Arqam Gombara selected as sample and 274 studentsof SMAN 6 selected proportional stratified random sampling. The analysis used univariate and bivariate analysiswith chi-square test and phi test. The result of the research shows that there is influence of parent role in MA DarulArqam (p=0,000, φ=0,403) to santri risk sexual behavior whereas student in SMAN 6 there is no influence ofparent role (p=0,472) towards sexual risk behavior. The influence of religious understanding (p=0.027, φ=0.134),peers (p=0,000, φ=0.339) and social media (p=0.035, φ=0.128) in SMAN 6 on risky sexual behavior in studentswhereas in MA Darul Arqam showed no influence of religious understanding (0,811), peer role (0,702) and socialmedia (0,063) toward risky sexual behavior at santri.